2008
DOI: 10.1097/opx.0b013e31818e8abe
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Ocular Hysteresis, Corneal Thickness, and Intraocular Pressure

Abstract: Diurnal variation of CH was not detectable in healthy Asian eyes. The diurnal fluctuation of IOP appears not to be associated with CH. However, CRF was increased a few minutes after sleeping, a change that was correlated to the changes of IOPg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…Kida et al 3 found that corneal hysteresis (CH) measured with a dynamic bidirectional applanation device (Ocular Response Analyzer, Reichert Technologies) showed an inconsistent 24-hour variation, with no evidence of being influenced by 24-hour changes in IOP. A similar finding was reported by Shen et al 4 However, Gonz alez-M eijome et al 5 found that changes in CH measured with the same device correlated well with changes in IOP, suggesting that diurnal IOP variations could be related to changes in corneal biomechanics. Likewise, Lau and Pye 6 suggested that diurnal variations in central corneal thickness (CCT) and corneal resistance factor (CRF) measured with the dynamic bidirectional applanation device may significantly affect the tonometry measurements.…”
supporting
confidence: 54%
“…Kida et al 3 found that corneal hysteresis (CH) measured with a dynamic bidirectional applanation device (Ocular Response Analyzer, Reichert Technologies) showed an inconsistent 24-hour variation, with no evidence of being influenced by 24-hour changes in IOP. A similar finding was reported by Shen et al 4 However, Gonz alez-M eijome et al 5 found that changes in CH measured with the same device correlated well with changes in IOP, suggesting that diurnal IOP variations could be related to changes in corneal biomechanics. Likewise, Lau and Pye 6 suggested that diurnal variations in central corneal thickness (CCT) and corneal resistance factor (CRF) measured with the dynamic bidirectional applanation device may significantly affect the tonometry measurements.…”
supporting
confidence: 54%
“…First, there exists a diurnal variation of IOP, known to be 3 to 4 mm Hg in healthy subjects, with the highest values typically in the early morning. 13,24,25 There was slight variability of start times of the surgeries. With the small diurnal fluctuation of IOP relative to the large increase described in the results, it is unlikely that diurnal variation significantly changes the findings.…”
Section: Resultsmentioning
confidence: 97%
“…The age dependency of the biomechanical parameters is also well known from the literature, 5, [20][21][22][23] conforming that the elastic properties of the cornea are changing with age. 23 On the contrary, others found that CH and CRF are very independent of age.…”
Section: Correlation Datamentioning
confidence: 87%